Mycoplasma Hyorhinis in the Etiology of Serositis among Piglets - Eriis, N. E (Acta Vet Scand, 1994)
In a study on the involvement of Mycoplasma hyorhinis in serositis of piglets, 26 routine diagnostic animals, 3-7 weeks old, with distinct serofibrinous lesions in the pericardial, pleural and peritoneal cavities were examined. M. hyorhinis was isolated in 9 cases, non-haemolytic Escherichia coli in another 9 cases and in 4 cases both species were found. Neither of the microorganisms were found in the remaining 4 cases. The presence of M. hyorhinis in the serous cavities in the absence of non-haemolytic E. coli was always accompanied by a diagnosis of other disease conditions, mainly of the respiratory tract. In the cases infected with non-haemolytic E. coli complicating problems were absent. The pathogenicity of M. hyorhinis was further studied by inoculation of 2 young pigs in which the typical serofibrinous lesions of the serous cavities were produced. It therefore appears that M. hyorhinis can be regarded as a cause of polyserositis in piglets; under field conditions, however, the synergistic presence of other debilitating syndromes appears necessary for its haematogenous spread from the respiratory tract to the serous cavities.